Early Repetitive Transcranial Magnetic Stimulation Exerts Neuroprotective Effects and Improves Motor Functions in Hemiparkinsonian Rats. (27th December 2021) - Hsieh, Tsung-Hsun; He, Xiao-Kuo; Liu, Hui-Hua; Chen, Jia-Jin J.; Peng, Chih-Wei; Liu, Hao-Li; Rotenberg, Alexander; Chen, Ko-Ting; Chang, Ming-Yuan; Chiang, Yung-Hsiao; Chang, Pi-Kai; Kuo, Chi-Wei
Abstract : Repetitive transcranial magnetic stimulation (rTMS) is a popular noninvasive technique for modulating motor cortical plasticity and has therapeutic potential for the treatment of Parkinson's disease (PD). However, the therapeutic benefits and related mechanisms of rTMS in PD are still uncertain. Accordingly, preclinical animal research is helpful for enabling translational research to explore an effective therapeutic strategy and for better understanding the underlying mechanisms. Therefore, the current study was designed to identify the therapeutic effects of rTMS on hemiparkinsonian rats. A hemiparkinsonian rat model, induced by unilateral injection of 6-hydroxydopamine (6-OHDA), was applied to evaluate the therapeutic potential of rTMS in motor functions and neuroprotective effect of dopaminergic neurons. Following early and long-term rTMS intervention with an intermittent theta burst stimulation (iTBS) paradigm (starting 24 h post-6-OHDA lesion, 1 session/day, 7 days/week, for a total of 4 weeks) in awake hemiparkinsonian rats, the effects of rTMS on the performance in detailed functional behavioral tests, including video-based gait analysis, the bar test for akinesia, apomorphine-induced rotational analysis, and tests of the degeneration level of dopaminergic neurons, were identified. We found that four weeks of rTMS intervention significantly reduced the aggravation of PD-related symptoms post-6-OHDA lesion. Immunohistochemically, the results showed that tyrosine hydroxylase- (TH-) positive neurons in the substantia nigra pars compacta (SNpc) and fibers in the striatum were significantly preserved in the rTMS treatment group. These findings suggest that early and long-term rTMS with the iTBS paradigm exerts neuroprotective effects and mitigates motor impairments in a hemiparkinsonian rat model. These results further highlight the potential therapeutic effects of rTMS and confirm that long-term rTMS treatment might have clinical relevance and usefulness as an additional treatment approach in individuals with PD.